Scalable, washable and lightweight triboelectric-energy-generating fibers by the thermal drawing process for industrial loom weaving. (August 2020) - Feng, Ziang; Yang, Shuo; Jia, Sixian; Zhang, Yujing; Jiang, Shan; Yu, Li; Li, Rui; Song, Guowen; Wang, Anbo; Martin, Thomas; Zuo, Lei; Jia, Xiaoting
Abstract: In the era of the internet of things (IoTs), it is desired to equip the decentralized electronics with distributed power sources. The fiber-based triboelectric nanogenerator (FTENG) provides one of the soundest solutions due to its high efficiency, easy deployment, excellent wearability, low cost, and eco-friendliness. Compared with other forms of TENGs, it can be woven into fabrics as wearable devices, offering good compactness and comfortability. However, the industrial-loom-compatible FTENGs have yet to be fabricated; the fiber diameter and length are typical challenges in the large scale weaving. In this paper, the thermal drawing process (TDP) is introduced to produce FTENGs that are compatible with industrial looms. The diameter of the polymer-cladding and metal-core fiber has been reduced to 350 μm, and the length of a single fiber has been scaled up to sub-kilometer. Both hand-woven and loom-woven swatches are demonstrated, showing good flexibility, stretchability, power density, stability, washability, and breathability. Besides serving as power sources, such swatches have been used as self-powered sensors for body motion monitoring and communication. These applications show that the thermally drawn FTENGs can serve as powerful and reliable wearable devices in modern electronics. Graphical abstract: Image 1 Highlights: The scalable thermal drawing method is introduced to the fiber-based triboelectric nanogenerator fabrication. The diameter of the fiber is down to 350 μm. The length of a single fiber is up to 200 m. The fabrication speed is up to 4 m min −1 . The thermally drawn fiber is compatible with industrial looms for weaving.